Dreams of El Dorado : a history of the American West - Brands, H. W (Basic Books, 2019)
In Dreams of El Dorado, H. W. Brands tells the thrilling, panoramic story of the settling of the American West. He takes us from John Jacob Astor's fur trading outpost in Oregon to the Texas Revolution, from the California gold rush to the Oklahoma land rush. He shows how the migrants' dreams drove them to feats of courage and perseverance that put their stay-at-home cousins to shame-and how those same dreams also drove them to outrageous acts of violence against indigenous peoples and one another. The West was where riches would reward the miner's persistence, the cattleman's courage, the railroad man's enterprise; but El Dorado was at least as elusive in the West as it ever was in the East.